Lectotypification of the name Carex delavayi (Cyperaceae) - Lu, Yi-Fei; Jin, Shui-Hu; Jin, Xiao-Feng (Phytotaxa, 2020)
We found that the original material of Carex delavayi Franch., a set of specimens that shares the same collector (Delavay) and collection number (1739), represents at least three different gatherings. According to the Shenzhen Code of ICN these specimens are to be considered syntypes. We perform the pertinent lectotypification on the specimen with the herbarium barcode P00281352 in P, collected from Nienkaise near Ta pin tze on 22 August 1885.